Education, income, and obesity: A nationwide Chinese twin study. Issue 4 (11th March 2022) - Zheng, Ke; Gao, Wenjing; Cao, Weihua; Lv, Jun; Yu, Canqing; Wang, Shengfeng; Huang, Tao; Sun, Dianjianyi; Liao, Chunxiao; Pang, Yuanjie; Pang, Zengchang; Yu, Min; et al.
Abstract: Objective: This study aimed to examine the association of socioeconomic status with obesity. Methods: A total of 39, 262 twin individuals were included from the Chinese National Twin Registry (CNTR). Generalized estimating equation models for unmatched twin individual analyses and conditional logistic regression for the co‐twin matched design were used. Inference about Causation through Examination of FAmiliaL CONfounding (ICE FALCON) was used to explore the evidence of a causal relationship. Results: In general estimating equation models, high education level and income were associated with lower risk of obesity (odds ratio [OR] = 0.74 [95% CI: 0.65 to 0.84] and 0.86 [95% CI: 0.77 to 0.96]). In conditional logistic regression analysis, the association with education was significant (OR = 0.50 [95% CI: 0.34 to 0.74]) but the association with income was insignificant (OR = 0.74 [95% CI: 0.48 to 1.15]). From the ICE FALCON analysis, a twin's obesity was associated with the co‐twin's education and income. After adjusting for the twin's own education, the association disappeared ( β co ‐ twin ′ = −0.10 [95% CI: −0.26 to 0.07]), whereas the twin's obesity was still associated with the co‐twin's income but attenuated toward the null ( β co ‐ twin ′ = −0.21 [95% CI: −0.36 to −0.06]). Conclusions: Socioeconomic status is negatively associated with obesity. Education may have a causal effect on obesity, whereas the association between income and obesity is confounded by familial factors.